Aptamer-based Advances in Skin Cancer Research - Piasek, Adrianna M.; Musolf, Paulina; Sobiepanek, Anna (Current Medicinal Chemistry, 2023)
Cancer diseases have been one of the biggest health threats for the last two decades. Approximately 9% of all diagnosed cancers are skin cancers, including melanoma and non-melanoma. In all cancer cases, early diagnosis is essential to achieve efficient treatment. New solutions and advanced techniques for rapid diagnosis are constantly being sought. Aptamers are single-stranded RNA or DNA synthetic sequences or peptides, which offer novel possibilities to this area of research by specifically binding selected molecules, the so-called cancer biomarkers. Nowadays, they are widely used as diagnostic probes in imaging and targeted therapy. In this review, we have summarized the recently made advances in diagnostics and treatment of skin cancers, which have been achieved by combining aptamers with basic or modern technologies.
Keywords: imaging methods